Transparency for Robots and Autonomous Systems : Fundamentals, Technologies and Applications - Wortham, Robert H. (The Institution of Engineering and Technology, 2020)
Based on scientific understanding and empirical evidence of how humans understand and interact with robotic and autonomous systems, this book reviews the concerns that have been raised around the deployment of AI and robots in human society, and the potential for disruption and harm.
Keywords: Artificial intelligence.; Autonomous robots.; elektronické knihy; electronic books